2019
DOI: 10.1002/pc.25464
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and mechanical properties, free volume, and γ‐ray transmission of ethylene propylene diene monomer/butadiene rubber composites

Abstract: Mechanism of electrical conductivity (σ), mechanical properties, and γ‐ray transmission properties of ethylene propylene diene monomer (EPDM)/butadiene rubber (BR) composites have been investigated from the viewpoint of free volume (ie, open hole size). The EPDM/BR composites (100/0, 70/30, 50/50, 30/70, and 0/100) loaded with 50 phr carbon black as a reinforcing filler and irradiated with different doses (10, 30, 50, 70, and 100 kGy). The ortho‐positronium lifetime (o‐Ps) for all the composites is measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 80 publications
(84 reference statements)
2
13
0
Order By: Relevance
“…It is clear from the figure that, the correlation is linear and the σ DC increases with the increasing of the free volume size indicating that the ionic conductivity of NaI/PVA composites is controlled by the free volume size. This behavior is similar to that obtained data by Mohamed et al 80 for the unirradiated samples of different concentrations of the polybutadiene rubber in ethylene propylene diene monomer. In addition, it is consistent with the reported measurements by El‐Gamal et al 81 found that the ionic conductivity of the polymeric sample increases with the increasing of the free volume as a result of the addition of polyaniline to PVA.…”
Section: Resultssupporting
confidence: 91%
“…It is clear from the figure that, the correlation is linear and the σ DC increases with the increasing of the free volume size indicating that the ionic conductivity of NaI/PVA composites is controlled by the free volume size. This behavior is similar to that obtained data by Mohamed et al 80 for the unirradiated samples of different concentrations of the polybutadiene rubber in ethylene propylene diene monomer. In addition, it is consistent with the reported measurements by El‐Gamal et al 81 found that the ionic conductivity of the polymeric sample increases with the increasing of the free volume as a result of the addition of polyaniline to PVA.…”
Section: Resultssupporting
confidence: 91%
“…The frequency ranged from 50 Hz to 5 MHz, and the measurements began at that point. The out‐of‐plan of the AC proton conductivity σ AC can be obtained as, 22,23 Proton conductivity0.25emσAC()normalS/normalmgoodbreak=L0.25emnormalG0.25em0.25emA. where L and A is the membrane thickness and the cross‐sectional area of the electrodes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, polymer-filler interface might cause in the absorption of the polymer chains on the filler surface and reduces its progress. Consequently, the polymer viscosity and modulus will be increased [46,47].…”
Section: Tensile Test Measurementsmentioning
confidence: 99%